ARTI “AIR DAN IKAN” MENURUT KODE BAHASA, SASTRA, DAN BUDAYA - Sangidu Sangidu (Arabic Literature Department, 2017)
The water and the fish have different meanings because of a lingual difference, literary, and cultural code that bounds them. This paper aims to discover these meanings and uses to realize this aim convenient theories and methods that are semiotic. The semiotic theories are all studies that examine all of the communication forms using the codes based on lingual, literary, and cultural codes. This semiotic framework consists of two principal elements namely signifier and signified. The method used to solve this problem is by heuristic and hermeneutic reading conducted simultaneously. The result of this paper reveals that the term of water indicates the following several meanings: the source of very vital life, the pure heart, the patience and power of the marginalized populaces, and flowing naturally down forever, and that the term of fish signifies the meanings of very high protein’s source needed by the body of human, entertaining the heart, and a symbol of a perfect person wishing to meet The God.